Actinellopsis murphyi gen. et spec. nov.: A new small celled freshwater diatom (Bacillariophyta, Eunotiales) from Zambia - Taylor, Jonathan Charles; Karthick, Balasubramanian; Kociolek, J. Patrick; Wetzel, Carlos E.; Cocquyt, Christine (Phytotaxa, 2014)
In this paper we describe Actinellopsis murphyi gen. et spec. nov. a small heteropolar and dorsiventral diatom from a seep habitat in Zambia. This novel taxon has the chief distinguishing characteristic, along with its cell symmetry, of having the raphe positioned wholly in the valve face and not extending onto the mantle. It is further placed within the Peroniaceae as it possesses a straight raphe on the valve face and rimoportulae, and the frustules are heteropolar with regard to the length of the raphe. We also transfer the fossil diatom Actinella giraffensis to Actinellopsis as the morphological characteristics of this taxon are consistent with those of the generitype.